1975
DOI: 10.1029/gl002i006p00251
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Farley‐Buneman Instability in laboratory plasma

Abstract: An experiment simulating certain characteristics of the equatorial electrojet plasma (viz. Ve»re Vi ≳ ri) is described. High frequency (W ≳ Vi > ri) instabilities are observed when electrons stream in the E × B direction past ions with a velocity exceeding the ion acoustic speed. The observed phase velocities and frequencies agree with the results of the Farley‐Buneman instability theory, modified to take account of finite k∥. The measured instability spectrum for potential fluctuations goes as k−n⊥ with n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
7
21
0
Order By: Relevance
“…In their experiment the phase velocity was supersonic for all cases, as supported also by other related experimental observations (D'Angelo et al, 1974;John and Saxena, 1975;Alport et al, 1981). Since these experiments were all carried out in a rotating cylindrical plasma column, it is plausible that the longest azimuthal wavelength ∼2π R, with R being the radius of the plasma column, was too small to reach the region of sonic or subsonic phase velocities.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…In their experiment the phase velocity was supersonic for all cases, as supported also by other related experimental observations (D'Angelo et al, 1974;John and Saxena, 1975;Alport et al, 1981). Since these experiments were all carried out in a rotating cylindrical plasma column, it is plausible that the longest azimuthal wavelength ∼2π R, with R being the radius of the plasma column, was too small to reach the region of sonic or subsonic phase velocities.…”
supporting
confidence: 54%
“…(1)- (2). The basic features of the Farley-Buneman instability are well understood, but a number of features are difficult to account for, in particular concerning a disagreement between the observations and results from several laboratory investigation (D'Angelo et al, 1974;John and Saxena, 1975;Mikkelsen and Pécseli, 1980). Several nonlinear saturation models have been suggested (Sudan, 1983;Primdahl and Bahnsen, 1985;Primdahl, 1986;Hamza and StMaurice, 1995), to account for the deviations between spaceobservation and what a simple extrapolation from the linear theoretical analysis seems to predict.…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced, anomalous collision frequency can give rise to a reduced phase velocity, which can be close to the ion acoustic speed (Primdahl, 1986;Primdahl and Bahnsen, 1985). It is interesting that laboratory experiments (John and Saxena, 1975;Mikkelsen and Pe cseli, 1980;Pe cseli et al, 1983) have shown dispersive properties of waves under conditions similar to those observed in the electrojet in the present study.…”
Section: Cross-phase Spectrummentioning
confidence: 64%
“…Electron-ion collisions have this effect, but in kinetic models electrons in resonance with the drift waves will also induce linear instability, although with modest growth rates. Plasma currents can enhance the instability (Kadomtsev, 1965). The theoretic results for the linear instability (the resistive instabilities, in particular) of drift waves have been confirmed to good accuracy by a number of laboratory experiments (Hendel et al, 1968;Rowberg and Wong, 1970;Rogers and Chen, 1970;Schlitt and Hendel, 1972), mostly in Q machines (Motley, 1975;Pécseli, 2012).…”
Section: Introductionmentioning
confidence: 69%
“…The current generated ion acoustic instability (i.e. an instability generated by an electron flow with velocity u relative to the ions) saturates at a moderate level of turbulent electrostatic fluctuations, and analytically it was found (Kadomtsev, 1965) that the power spectrum of the normalized electrostatic potential for u C s becomes…”
Section: Universal Spectra In a Weak-turbulence Modelmentioning
confidence: 99%